Homicídios no Estado da Bahia: Determinantes socioeconômicos e ambientais no período de 2000 a 2009 - Moura, Cláudio Luiz Araújo (2012)
The homicide mortality has gained prominence in debates about its magnitude in the sphere of national and more recently in the State of Bahia, this which passes for a growing increase in mortality from this cause. Given knowledge of the areas of Geosciences and Epidemiology, this research examined the mortality rate from homicides in the state of Bahia in the socioeconomic and environmental aspects in the period from 2000 to 2009. The data for the research were obtained from the SIM - Health Information System - DATASUS agency of the Ministry of Health and Brazilian Institute of Geography and Statistics (IBGE). The methodology consisted of a survey and analysis of bibliographic references that gave theoretical support for development of a database, making georeferenced maps, tables and graphs. In addition to the standardization of rates (direct method), we applied the negative binomial model with random effects to identify potential risk factors that were adopted after the application of the Hausman test, with the population of a sample analysis with the 50 more populous cities of the State. The analysis of the spatial distribution of mortality rates per 100 inhabitants by place of occurrence, made by choropleth maps of 417 cities and Territory of Identity, was performed using epidemiological indicators of homicide rates and considering the International Classification of Diseases - ICD in its 10th revision. These steps also allowed the preparation of a profile of homicide victims, taking into account the variables (sex, race / ethnicity, education, marital status and age). In analyzing the profile of the victims, it was found that the most victims were male (93.06%), young age (63.13%), race / black (83.43%), unmarried (88.19%), schooling less than 08 years of study (84.24%). The most used instrument consisted of a firearm (77.02%) and place of death was the most common street (42.82%). In the spatial distribution of rates for the 417 cities of Bahia, was found a descent of these rates during the studying period, especially in cities with rates above 27.0 per 100 000 (national average) in the coastal cities in the state and upstate. The West of Bahia presented low rates during the period. The Territory of Identity by spatial showed that, during the studying period there was a progressive increase in mortality rates per 100 thousand inhabitants, with apex in 2009 showed that 08 Territories Identity with rates above the national average. In the multivariate analysis of the determinants investigated in each block there were factors associated with the reduction of homicides (rate sanitation, schooling rate, proportion of white fertility rate) and increased (rate of water, population density - Iddem , proportion of mixed). In analyzing the intra-block distal the variable Gini index, showed total effect (IRR = 0.56 and 0.54) in relation to the homicide rate, but with the opposite direction than expected. The variable intermediate population density was mediated by more proximal factors, and its total effect (IRR = 1.94 and 2.28 - Model - A) and its effect unmediated (IRR = 1.71 and 1.78 - Model - B). Similar behavior was observed in the distal Gini factor whose effect was not mediated (IRR = 0.73 and 0.71 - Model - B).